THE ATTITUDE OF MERCHANTS TOWARDS FATWA ON RIBA AND CONVENTIONAL BANK IN LANGSA - Muhammad Dayyan; Rifyal Dahlawy Chalil (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
This research aims to analyze and examine the level of knowledge possessed by the merchants in the traditional market of Langsa on the concept of riba, the reasons (factors) the merchants transact with the conventional bank, and the attitude of merchants on fatwa given by the National Sharia Board of the Indonesian Ulema Council (DSN-MUI). The research population is an unknown population that consists of all market traders in Langsa City and the sample selected is 117 respondents. This research implements a non-probability sampling technique with purposive sampling as the method. The result shows that majority of the respondents has a profound understanding on the haram concept of interest (riba) and the role of DSN-MUI as the obligated council in setting the fatwa, which needs to be followed, yet the respondents do not mind interacting with the conventional banks in terms of getting business financing. They believe that riba (usury) is forbidden, yet they do not mind borrowing some amount of funds or saving their money in conventional banks, which implemented the interest-based system. More than 31 respondents (26,5%) perceive that interest is not the same as riba, and 50 respondents (42.7%) say that conventional bank is very helpful in promoting business. A more aggressive role is needed from the Sharia banks to reach all layers of society and educate as well as promote sharia-based banking products, especially financing products========================================================================================================Perilaku Pedagang terhadap Riba dan Fatwa tentang Bunga Bank Konvensional di Langsa Aceh. Penelitian ini bertujuan untuk menganalisis dan menguji tingkat pengetahuan yang dimiliki oleh para pedagang di pasar tradisional Langsa terhadap konsep riba, alasan (faktor) mereka melakukan transaksi dengan bank konvensional, dan sikap para pedagang terhadap fatwa yang dikeluarkan oleh Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI). Sebanyak 117 responden telah dipilih sebagai sampel dari seluruh pedagang di Kota Langsa sebagai populasi yang tidak diketahui jumlahnya. Pengambilan sampel menerapkan teknik non probability sampling dengan metode purposive sampling. Hasilnya menunjukkan bahwa mayoritas responden memiliki pemahaman yang mendalam tentang konsep riba dan peran DSN-MUI sebagai dewan yang wajib menetapkan dan mengeluarkan fatwa dan perlu diikuti oleh masyarakat. Meskipun demikian responden tidak keberatan berinteraksi dengan bank konvensional dalam hal mendapatkan pembiayaan bisnis. Mereka percaya bahwa riba dilarang, namun mereka tidak keberatan meminjam sejumlah dana atau menyimpan uang mereka di bank konvensional, yang menerapkan sistem berbasis bunga. Lebih dari 31 responden (26,5%) merasa bahwa bunga tidak sama dengan riba, dan 50 responden (42,7%) mengatakan bahwa bank konvensional sangat membantu dalam mempromosikan bisnis. Peran yang lebih agresif diperlukan dari bank-bank Syariah untuk menjangkau semua lapisan masyarakat dan mengedukasi serta mempromosikan produk-produk perbankan berbasis syariah, terutama produk-produk pembiayaan.